Analysis of one-strut failure for deep excavations - Ang, Erland (2011)
This report presents the analysis of the behavior of braced excavation for the situation of one-strut failure by carrying out parametric finite element study on a typical soft clay layer underlain by stiff soil strata. The study focuses on the effect of one-strut failure on braced excavation performance in terms of lateral wall displacement, bending moment, and strut loads. Both plane strain and three-dimensional model finite element analyses were carried out and the results are compared. The modeled braced excavation is 16 m deep and is supported by five levels of struts. The influences of the wall system stiffness from flexible to stiff walls were considered. Some additional cases are studied for braced excavation with different failed-strut location.